Coagulation Factor X Regulated by CASC2c Recruited Macrophages and Induced M2 Polarization in Glioblastoma Multiforme - Zhang, Yan; Feng, Jianbo; Fu, Haijuan; Liu, Changhong; Yu, Zhibin; Sun, Yingnan; She, Xiaoling; Li, Peiyao; Zhao, Chunhua; Liu, Yang; Liu, Tao; Liu, Qiang; et al. (Frontiers in Immunology, 2018)
Tumor-associated macrophages (TAMs) constitute a major component of inflammatory cells in the glioblastoma multiforme (GBM) tumor microenvironment. TAMs have been implicated in GBM angiogenesis, invasion, local tumor recurrence and immunosuppression. Coagulation factor X (FX) is a vitamin K-dependent plasma protein that plays a role in the regulation of blood coagulation. In this study, we first found that FX was highly expressed and positively correlated with TAM density in human GBM. FX exhibited a potent chemotactic capacity to recruit macrophages and promoted macrophages toward M2 subtype polarization, accelerating GBM growth. FX bound to ERK1/2 and inhibited p-ERK1/2 in GBM cells. FX was secreted in the tumor microenvironment and increased the phosphorylation and activation of ERK1/2 and AKT in macrophages, which may have been responsible for the M2 subtype macrophage polarization. Moreover, although the lncRNA CASC2c has been verified to function as a miR-101 ceRNA to promote miR-101 target genes in GBM cells, we first confirmed that CASC2c did not function as a miR-338-3p ceRNA to promote FX expression, and that FX was a target gene of miR-338-3p. CASC2c interacted with and reciprocally repressed miR-338-3p. Both CASC2c and miR-388-3p bound to FX and commonly inhibited its expression and secretion. CASC2c repressed M2 subtype macrophage polarization. Taken together, our findings revealed a novel mechanism highlighting CASC2c and FX as potential therapeutic targets to improve GBM patients by altering the GBM microenvironment.